2020
DOI: 10.1002/adbi.202000247
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Materials for Stem Cell Differentiation

Abstract: Traditionally, understanding differentiation pathway has been achieved by studying biochemical signal pathways controlled by various growth factors and cytokines. However, since various physical factors including tissue stiffness and topology can also determine the differentiation pathway of stem cells, mechanobiological pathway for controlling differentiation has been emphasized. Moreover, newly identified mechanobiological pathways have encouraged efforts to interpret stem cell differentiation in terms of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 136 publications
0
65
0
Order By: Relevance
“…Recent literature has focused on the paramount role of the ECM mechanical properties in controlling stem/progenitor cells' behavior, including maintaining their potency, self-renewal and differentiation, migration, proliferation, and interaction with other cells [39,40]. Matrix-related mechanical stimuli, including strain, shear stress, matrix rigidity, and topography, could impact stem/progenitor cell phenotypes through controlling gene transcription and signaling pathways [40,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has focused on the paramount role of the ECM mechanical properties in controlling stem/progenitor cells' behavior, including maintaining their potency, self-renewal and differentiation, migration, proliferation, and interaction with other cells [39,40]. Matrix-related mechanical stimuli, including strain, shear stress, matrix rigidity, and topography, could impact stem/progenitor cell phenotypes through controlling gene transcription and signaling pathways [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, inducing transcription factors to control and guide MSCs' differentiation has become an essential strategy for guided tissue regeneration [26]. Interference between signaling pathways through interaction between different transcription factors can drive MSCs towards specific cell linage; for example, osteogenic signaling can inhibit the adipogenic signaling pathway, and vice versa [41].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that the soft matrix induced chondrogenesis, while the hard matrix encouraged osteogenesis. [ 35,36 ] Therefore, the feasibility of the PU scaffolds in tissue engineering was evaluated by in vitro study for bone regeneration. Before the in vitro study, the biodegradation property of the PU scaffolds was evaluated under the accelerated hydrolysis condition using NaOH solution (50 mmol) at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These modifications adjust the cell-material interactions, which affect intracellular pathways regulating cellular behavior. 109 Material stiffness is the resistance of materials to deformation when a force is applied, which means that the materials with high stiffness can resist deformation, but materials with low stiffness, deform easily. Every tissue displays a special stiffness value, which is determined by the composition of the ECM and cross-linking proteins.…”
Section: Materials Advancesmentioning
confidence: 99%
“…Consequently, these interactions convert to biochemical signals, which determine the cell behaviors and stem cell fate. 109,111,112 Several studies revealed that mimicking the biomechanical properties of cardiac muscles is crucial in cardiac tissue engineering. First, the biomechanical cues may induce cardiac differentiation.…”
Section: Materials Advancesmentioning
confidence: 99%